Strength Analysis of Horizontal Type Wind Turbine Blades Using PVC Pipe Material - Radik Kemala Ali; Jumiadi Jumiadi (TRANSMISI, 2022)
The wind defines as air moves from one place to another which produces kinetic energy. Wind moves due to pressure differences that affect the temperature in a region on the earth’s surface. The utilization of wind turbines as the renewable energy is not maximal. This research was focused on understanding the strength of wind turbine spoons which using PVC pipe material. The tensile test was conducted on 5 specimens that used 1 type of PVC and different variations in wind speed ranging from 3 m/s -7 m/s and the results showed that specimen 1 with wind speed of 3 m/s was 18.30 kg/mm2, specimen 2 with wind speed of 4 m/s was 19.32 kg/mm2, specimen 3 with wind speed of 5 m/s was 21.28 kg/mm2, specimen 4 with wind speed of 6 m/s was 22.01 kg/mm2, and specimen 5 with wind speed of 7 m/s was 19.32 kg/mm2.